2022
DOI: 10.3390/vaccines10071067
|View full text |Cite
|
Sign up to set email alerts
|

Rare Adverse Events Associated with BNT162b2 mRNA Vaccine (Pfizer-BioNTech): A Review of Large-Scale, Controlled Surveillance Studies

Abstract: Given the increasing anti-vaccine movements erroneously touting vaccine danger, this review has investigated the rare adverse events potentially associated with BNT162b2 (Pfizer-BioNTech), an mRNA vaccine against the severe acute respiratory distress syndrome coronavirus 2 (SARS-CoV-2). Only real-world surveillance studies with at least 0.1 million BNT162b2-vaccinated participants and one unvaccinated control group were selected for review. A total of 21 studies examining the potential association of BNT162b2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
1
6
1
Order By: Relevance
“…Notably, among these were nine acute myocardial infarctions, five pulmonary embolisms, and one case in which the causes of death could not be determined. However, the lack of epidemiological support (47,49), and the fact that more plausible etiologies were present (e.g. malignancy in case of pulmonary embolism) argue against a significant proportion of true vaccine-related deaths in our study.…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…Notably, among these were nine acute myocardial infarctions, five pulmonary embolisms, and one case in which the causes of death could not be determined. However, the lack of epidemiological support (47,49), and the fact that more plausible etiologies were present (e.g. malignancy in case of pulmonary embolism) argue against a significant proportion of true vaccine-related deaths in our study.…”
contrasting
confidence: 62%
“…As with pulmonary embolism, Botton et al (47) found an increase in the risk for myocardial infarction after the first dose of ChAdOx1 (relative incidence 1.29, confidence interval 1.11–1.51), and after Ad26.COV2.S (relative incidence 1.75, confidence interval 1.16–2.62), but not with the mRNA-type vaccines. Again, no increased risk for myocardial infarction arose in connection with BNT162b2 in other large study settings as reviewed by Yong et al (49). Hence, although COVID-19 vaccination was, according to the medicolegal assessment, considered a potential etiological factor for pulmonary embolism in three of our cases and myocardial infarction in one case, all vaccinated with BNT162b2, we found no epidemiological evidence to support these decisions.…”
Section: Discussionmentioning
confidence: 80%
“…75 Despite the known risks of COVID-19 vaccines (e.g., mRNA vaccine-related myocarditis and DNA vaccine-related thrombotic thrombocytopaenia), current consensus agrees that the overall risk-benefit ratio still favours the benefit. [76][77][78][79][80] Furthermore, in light of the increase in certain immune and vascular biomarkers in PCS found in our meta-analysis, therapies targeting these biomarkers may hold potential for treating PCS. For instance, antithrombotic therapy such as heparin may be used to treat PCS patients with elevated D-dimer.…”
Section: Discussionmentioning
confidence: 75%
“…A meta‐analysis calculated that vaccinated individuals (against COVID‐19) had a 29% lower relative risk of developing PCS compared to unvaccinated individuals, with subgroup analyses showing that this effect remained with vaccination before or after COVID‐19 75 . Despite the known risks of COVID‐19 vaccines (e.g., mRNA vaccine‐related myocarditis and DNA vaccine‐related thrombotic thrombocytopaenia), current consensus agrees that the overall risk‐benefit ratio still favours the benefit 76–80 . Furthermore, in light of the increase in certain immune and vascular biomarkers in PCS found in our meta‐analysis, therapies targeting these biomarkers may hold potential for treating PCS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, real-world surveillance studies to monitor the safety and effectiveness of COVID-19 vaccines have been published. 5 A recent study 6 based on the pharmacovigilance post-marketing database of the World Health Organization reported the occurrence of 103,954 adverse events among 30,523 patients between December 15, 2020, and January 24, 2021. A total of 4201 (4%) cardiovascular adverse events from the Pfizer-BioNTech vaccine were reported, and the most common complications were tachycardia, flushing, and hypertension.…”
mentioning
confidence: 99%